Impact of a national HPV vaccination programme for preadolescent girls on cytology screening performance and CIN2+ incidence: five-year population-based cervical screening results from Slovenia - Irzaldy, Abyan; de Kok, Inge M. C. M.; Hontelez, Jan; de Koning, Harry J.; Jansen, Erik E. L.; Ivanuš, Urška (The lancet. Regional health, 2025)
Background - HPV vaccination is most efficacious in preventing cervical cancer and its precursors when administered during preadolescence. Because in Slovenia women are invited for cytology screening from age 20, women targeted for preadolescent HPV vaccination have been screening-eligible since 2018. We aim to assess the impact of preadolescent HPV vaccination programme on cytology screening performance and CIN2+ incidence. - Methods - This is a cohort study using data from Slovenia's cervical screening registry. We compared the incidence of high-grade lesions (CIN2 or worse) between women in the first vaccine-targeted birth cohort (1998-2001) and in the latest non-vaccine-targeted birth cohort (1994-1997). We calculated the Incidence Rate Ratio (IRR) of CIN2+ using Poisson regression. To identify a possible shift in the harms-benefits ratio of screening, we compared the following screening performance indicators using chi-square tests: colposcopy referral rate (CRR), positive predictive value (PPV) of low-grade and high-grade results, and CIN2+ detection rate. - Findings - The annual quadrivalent vaccine coverage in vaccine-targeted cohort was between 48.7% and 55.2%. The CIN2+ incidence was substantially lower in vaccine-targeted cohort (IRR 0.58 95% CI 0.49-0.69). Screening indicators were significantly lower for the vaccine-targeted cohort: direct CRR (0.47% [118/25,185] vs. 0.68% [206/30,181]), PPV (26.8% [30/112] vs. 39.0% [76/195]), and CIN2+ detection rate (0.31% [79/25,185] vs. 0.55% [165/30,181]) (p < 0.05). - Interpretation - Even under imperfect vaccination coverage of around 50%, CIN2+ incidence in the vaccine-targeted cohort was observed to be 42% lower. Furthermore, the harms-benefits ratio of cervical screening deteriorates, marked by lower PPV and detection rate. This warrants an adaptation in screening algorithms in vaccinated cohorts. - Funding - European Union Horizon 2020.